The cerebrospinal fluid "Alzheimer profile": Easily said, but what does it mean?. Issue 6 (9th April 2014) - Duits, Flora H.; Teunissen, Charlotte E.; Bouwman, Femke H.; Visser, Pieter‐Jelle; Mattsson, Niklas; Zetterberg, Henrik; Blennow, Kaj; Hansson, Oskar; Minthon, Lennart; Andreasen, Niels; Marcusson, Jan; Wallin, Anders; et al.
Abstract: Background: We aimed to identify the most useful definition of the "cerebrospinal fluid Alzheimer profile, " based on amyloid‐ß1‐42 (Aβ42 ), total tau, and phosphorylated tau (p‐tau), for diagnosis and prognosis of Alzheimer's disease (AD). Methods: We constructed eight Alzheimer profiles with previously published combinations, including regression formulas and simple ratios. We compared their diagnostic accuracy and ability to predict dementia due to AD in 1385 patients from the Amsterdam Dementia Cohort. Results were validated in an independent cohort (n = 1442). Results: Combinations outperformed individual biomarkers. Based on the sensitivity of the best performing regression formulas, cutoffs were chosen at 0.52 for the tau/Aβ42 ratio and 0.08 for the p‐tau/Aβ42 ratio. Ratios performed similar to formulas (sensitivity, 91%–93%; specificity, 81%–84%). The same combinations best predicted cognitive decline in mild cognitive impairment patients. Validation confirmed these results, especially regarding the tau/Aβ42 ratio. Conclusions: A tau/Aβ42 ratio of >0.52 constitutes a robust cerebrospinal fluid Alzheimer profile. We recommend using this ratio to combine biomarkers.